2019
DOI: 10.3847/1538-4357/aaef87
|View full text |Cite
|
Sign up to set email alerts
|

The Formation Conditions of the Wide Binary Class 0 Protostars within BHR 71

Abstract: We present a characterization of the binary protostar system that is forming within a dense core in the isolated dark cloud BHR71. The pair of protostars, IRS1 and IRS2, are both in the Class 0 phase, determined from observations that resolve the sources from 1 µm out to 250 µm and from 1.3 mm to 1.3 cm. The resolved observations enable the luminosities of IRS1 and IRS2 to be independently measured (14.7 and 1.7 L , respectively), in addition to the bolometric temperatures 68 K, and 38 K, respectively. The sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 101 publications
3
30
0
Order By: Relevance
“…An inclination angle of 90 degrees indicates an edge-on system, and inclination greater than 90 degrees indicates the rotation vector is behind the plane of sky. High resolution ALMA 13 CO observations also indicate an inclination angle between 115 • to 153 • under the same definition (Tobin et al 2019). BHR 71 also shows prominent outflows in the north-south direction (Bourke et al 1997), resulting in several active shocked regions (Garay et al 1998;Gusdorf et al 2011Gusdorf et al , 2015.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…An inclination angle of 90 degrees indicates an edge-on system, and inclination greater than 90 degrees indicates the rotation vector is behind the plane of sky. High resolution ALMA 13 CO observations also indicate an inclination angle between 115 • to 153 • under the same definition (Tobin et al 2019). BHR 71 also shows prominent outflows in the north-south direction (Bourke et al 1997), resulting in several active shocked regions (Garay et al 1998;Gusdorf et al 2011Gusdorf et al , 2015.…”
Section: Introductionmentioning
confidence: 94%
“…BHR 71 is a Bok globule near the Southern Coalsack at 200 pc (Seidensticker & Schmidt-Kaler 1989;Straizys et al 1994), hosting two protostars, IRS1 and IRS2, separated by 16 (Bourke 2001;Tobin et al 2019). Tobin et al (2019) detect opposite velocity gradients toward IRS1 and IRS2, suggesting that the binary system is likely formed via turbulent fragmentation. BHR 71 IRS1 dominates the luminosity of BHR 71 with L = 13.5 L (Yang et al 2018), whereas IRS2 only has 1.7 L (Tobin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained M cr = 14.5 − 18.7 M ⊙ with M BE 8.5 M ⊙ . The Bonnor-Ebert mass was estimated using a kinematic temperature T kin of 13 K (Bourke et al 1995b), a turbulent velocity dispersion of 0.2 km s −1 (Tobin et al 2019), and an assumed external pressure of 6 × 10 4 K cm −3 . The assumed external pressure is equivalent to T eff × ρ, where ρ is the mean density of the core and T eff is the sum of the kinematic temperature T kin and the turbulence equivalent temperature T turb = µ p σ 2 turb /k = 10.9 K. The mean molecular weight per free particle µ p is set to 2.33 and k is the Boltzmann constant.…”
Section: Magnetic Properties Of the Core And The Origin Of The Curvedmentioning
confidence: 99%
“…These protostars have misaligned outflows (Bourke 2001;Parise et al 2006). Furthermore, Tobin et al (2019) reported that the rotation of these protostars measured in C 18 O (J = 1 − 0) on scales of < 1000 au around each source is in the opposite direction. These results may be evidence these protostars formed by turbulent fragmentation (Tobin et al 2019), and is consistent with a theoretical simulation of the formation of binary/multiple sources in turbulent environments (Offner et al 2016).…”
Section: Introductionmentioning
confidence: 98%